2018
DOI: 10.1002/jper.18-0066
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tunnel technique in the treatment of localized and multiple gingival recessions: A systematic review and meta‐analysis

Abstract: TUN is an effective procedure in treating localized and multiple GR defects. Limited evidence is available comparing TUN to CAF; however, CAF seemed to be associated with higher percentage of CRC than was TUN when the same grafts (connective tissue or acellular dermal matrix) were used in both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
3
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(170 citation statements)
references
References 49 publications
14
116
3
9
Order By: Relevance
“…The efficacy of root coverage procedures in treating gingival recessions on natural dentition have been well established . Additionally, the position of the interproximal attachment levels as the main limiting factor in the amount of root coverage that can be achieved, has also been confirmed …”
Section: Discussionmentioning
confidence: 95%
“…The efficacy of root coverage procedures in treating gingival recessions on natural dentition have been well established . Additionally, the position of the interproximal attachment levels as the main limiting factor in the amount of root coverage that can be achieved, has also been confirmed …”
Section: Discussionmentioning
confidence: 95%
“…• OpenGrey: using the following search strategy: (gingiva* AND (recession* OR defect*)) OR (root coverage) References from previous systematic reviews (Atieh et al, 2016;Buti et al, 2013;Cairo, Nieri, & Pagliaro, 2014;Cairo et al, 2016;Chambrone & Tatakis, 2015;Chambrone et al, 2018;Huang et al, 2019;Karam et al, 2016;Koop, Merheb, & Quirynen, 2012;Oliveira & Muncinelli, 2012;Tavelli et al, 2018) concerning root coverage procedures were checked for article screening. Authors of relevant grey literatures who could be reached by email have been contacted.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Tunneling (TUN) technique gained popularity with clinicians by offering minimally invasive surgery with acceptable root coverage and better esthetic outcomes. A recent review on the efficacy of TUN versus CAF indicated that the former was useful for both localized and MGARs, although, the latter was found to be associated with better root coverage (Tavelli et al, ).…”
Section: Introductionmentioning
confidence: 99%